Prevalence of human papillomavirus genotypes in low and high grade squamous intraepithelial lesions at cervical tissue - Prasetyo, Rizki Eko; Mastutik, Gondo; Mustokoweni, Sjahjenny (Folia Medica Indonesiana, 2017)
HPV infection is known to cause cervical cancer. This study aimed to identify the variant of HPV genotypes of cervical precancerous lesions from low grade squamous intraepithelial lesion (LSIL) and high grade squamous intraepithelial lesion (HSIL). This was an explorative study using formalin fix paraffin embedded (FFPE) from cervical precancerous lesions at Dr. Soetomo Hospital, Surabaya. DNA was extracted from FFPE and hybridized for HPV genotyping using Ampliquality HPV Type Express kit (AB ANALITICA) by reverse line blot techniques. The results showed that there were variants of HPV genotype in LSIL. The variants were HPV16 (8/15), HPV18 (3/15), HPV52 (1/15), HPV6+31 (1/15), HPV6+18 (1/15), and HPV72+68 (1/15), and in HSIL which were HPV16 (4/10), HPV18 (2/10), HPV59 (1/10), HPV6+45 (1/10), HPV61+26 (1/10), and HPV16+31 (1/10). The characteristics of infection in LSIL were single infection of high-risk (hr) HPV and multiple infection of low-risk (lr)+hr HPV, and in HSIL were single infection of HPVhr, multiple infection of HPVhr+hr and HPVlr+hr. In conclusion, HPV prevalence in cervical precancerous lesions is single infection by HPV16 (48%), HPV18 (20%), HPV52 (4%), HPV59 (4%), and multiple infection by HPV6+31, HPV6+18, HPV6+45, HPV16+31, HPV61+26, HPV72+68 is 4%.